Mrs. Morris and the venomous valentine - Wilton, Traci (Wilton, Traci. Salem B&B mystery, 2025)
A full house is nothing new to Charlene and her ghostly friend, Dr. Jack Strathmore, but this Valentine’s Day, their Salem, Massachusetts inn isn’t filled with romantic couples. Instead, every room is booked by formerly famous photographer, Dane Stallone, for a Cupid-themed calendar he hopes will jumpstart his sagging career. Though Charlene’s hands are full with a dozen gorgeous models, Dane is the only diva—pitching fits, making unreasonable demands, and generally being a mood killer . . . until a real killer strikes and puts the whole shoot on ice. With more suspects than a jumbo box of chocolates, Charlene, Jack, and Detective Sam Holden race to find the one person filled with murderous intent.